The Correlation Between Student’s Self-Confidence In Their Speaking Skill - Pratasik, Loviando; Maru, Mister Gidion; Rombepajung, Paula A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This research aims to find out the correlation between student’s self-confident in their speaking skill. This research was conducted at SMP N 8 Satap Tondano. Descriptive quantitative survey was the method used in this research and the instrument to collect data by using a questionnaire. The questionnaire distributed to 20 students. The result of this research showed that, most of the students give positive response to the statements about their reading habits. It can be seen through the their responses in questionnaire. The researcher concluded that the students of class 7,8 and 9 at SMP N 8 Satap Tondano, English Education Department of Universitas Negeri Manado who were the samples in this study like to improving their speaking skill, feel happy, and are also excited when answer the questionairre. It is expected that, this research can present information as reference material for the next researchers and English teachers in providing assistance, motivation to maintain good to improve teaching techniques, in order to increase and enhance their English speaking skills